Solid-state synthesis of pure belite polymorphs - Michal Křištof; Andrea Jančíková; Karel Dvořák (Acta Polytechnica CTU Proceedings, 2025)
The solid-state synthesis of pure belite polymorphs is still not described in detail. The study of this issue is important for understanding modification transformations, especially between beta and gamma modifications. In this paper, the two-step firing procedure was used to study belite transformations. The first firing step was designed to produce samples with high content of γ-C2S. These samples were fired again and successfully transformed into β-C2S without any additional chemicals. In addition to firing parameters, the effect of particle size was also monitored. The experiment succeeded in creating a sample containing 64 % gamma belite in total and also a sample containing a total of 90 % of beta belite.